Implementasi Sistem Monitoring Penjualan Berbasis Codeigniter (Study Kasus : IUS Aguaria Purwodadi - Grobogan) - Susanto, Susanto; Setiawan, Yogi Agus (Smart Comp :Jurnalnya Orang Pintar Komputer, 2023)
The monitoring system is an important system for every agency that trades and rents an item, often this monitoring activity determines whether the agency is running or not, because by monitoring, agency managers can find out how fast or slow the sale of an item is. With this system, stores or companies can process data more accurately. This monitoring system is excellent because in addition to the many benefits, the system can change the company for the better because of the results obtained from this system. The system at IUS is considered ineffective because the monitoring of data on goods and daily transactions along with reports is still done in writing by recording using books and paper, so this system is not efficient in saving time, energy and materials. With the problem in the system, a web-based monitoring system was created using CodeIgniter 3. In system development, the approach method used was a structured approach method using the RAD development method or Rapid Application Development, where the data collection techniques used were based on field observations and Interview result. While the result of making this system is the formation of a monitoring system that can make it easier to manage sales data, help employees to reduce errors in the reporting process and select/monitor the best-selling items in the store.The monitoring system is an important system for every agency that trades and rents an item, often this monitoring activity determines whether the agency is running or not, because by monitoring, agency managers can find out how fast or slow the sale of an item is. With this system, stores or companies can process data more accurately. This monitoring system is excellent because in addition to the many benefits, the system can change the company for the better because of the results obtained from this system. The system at IUS is considered ineffective because the monitoring of data on goods and daily transactions along with reports is still done in writing by recording using books and paper, so this system is not efficient in saving time, energy and materials. With the problem in the system, a web-based monitoring system was created using CodeIgniter 3. In system development, the approach method used was a structured approach method using the RAD development method or Rapid Application Development, where the data collection techniques used were based on field observations and Interview result. While the result of making this system is the formation of a monitoring system that can make it easier to manage sales data, help employees to reduce errors in the reporting process and select/monitor the best-selling items in the store.